Survey of prevalence and investigation of predictors and staining patterns of the split upper eyelid defect in Hebridean sheep. (12th August 2017) - Gascoigne, Emily; Williams, David L; Reyher, Kristen K
Abstract : The split upper eyelid defect (SUED) is a congenital defect of the upper eyelid thought to be exclusive to multihorned sheep. Eleven flocks with a high proportion of multihorned Hebridean sheep were visited in 2011. Statistical analysis was performed generating Pearson's chi‐squared analysis, as well as (1) logistic regression, (2) ordinal logistic regression and (3) linear regression models. Four hundred and seventy‐three pure‐bred Hebridean sheep and one crossbred lamb were examined. Of all the multihorned animals inspected in 2011, 9.7 per cent of adults had evidence of SUED in one or more eyelids, with 17.6 per cent of lambs presented with one or more eyelid affected. Having five or more horns was protective in the linear regression model on eye‐level data (p=0.045). Forward‐facing horns were consistently associated with a 'worst' eye score in the eye‐level data, with an odds ratio (OR) as high as 9.4 when compared with a base of backward‐facing horns (p=0.002). Eyes positive for SUED were significantly more likely to be rose bengal stain‐positive in all four analysis, including multilevel mixed effect ordered logistic regression (p<0.001, OR 149.3). A novel lesion was identified during the course of the study, with 3.4 per cent of lambs presented with dermoid. SUED was also identified in a crossbred animal. Further work is needed to quantify the exact cost to animals with unilateral or bilateral SUED with subtle and production cost of SUED.